Association of blood group types and clinico-pathological features of gynecological cancers (GCs) - Syed Sameer Aga; Muhammad Anwar Khan; Mubarak Al Mansour; Rana Mohammed Hasosah; Lulu Abdullah Alsubaie; Dala Ahmad Alfaify; Malak Badr Alansari; Shahad Obaidallah Almutairi; Saniya Nissar (BMC Cancer)
Abstract Background Gynecological cancers (GCs) affect the reproductive system of females, and are of multiple types depending on the affected organ most common of which are cervical, endometrial, ovarian cancers. Among different risk factors for GCs, ABO blood group system is considered as one of the pivotal contributing factors for increased susceptibility of GCs. The aim of our study was to report on the demographics of GC patients and to investigate the relationship between the ABO blood group system and the risk of acquiring GC in our population. Methods The current retrospective cross-sectional study was carried out between the years of 2016 and 2023. The sample included all the patients having age > 18 with a record of blood group and confirmed histological or cytological diagnosis as per International Federation of Gynecology and Obstetrics (FIGO) guidelines. A comprehensive review of the charts was conducted to gather data including demographics, tumor characteristics, comorbidities, adverse effects, and treatment methods. Results A total of 543 female patients were included in the study. The mean age of patients was 61.6. The three most common BG in our GC cases were as O + (43.8%), followed by A + (26%), and B + (15.5%). Among comorbidities, hypertension (HTN), diabetes mellitus (DM), dyslipidemia were the top three affecting GC patients. A significant association (p < 0.05) between ABO BG and serous histology in endometrial cancer was found. ABO blood group and fallopian cancer showed a significant relationship between serous histology and B blood group (p < 0.05). For ovarian cancer a significant association between AB blood group and recurrence rates were found (p < 0.05). In case of the patient dependent GCs, a significant association between ovarian cancers and recurrence, fallopian tube cancers and adverse events and survival status, vaginal/vulval cancers and TNM stage and mixed GCs and tumor type (carcinoma) was observed (P < 0.05). Furthermore, multinomial analysis between various confounding factors and GCs revealed that the risk of Cervical, Endometrial and Ovarian cancers to be significant for Type B BG (P < 0.05). Conclusion Our study found that O + BG was the most prevalent among our population. Furthermore, there was a significant association between BG B and endometrial and serous histology in fallopian tube and between BG AB and ovarian malignancies, respectively. Additionally, multinomial analysis revealed higher risk of Cervical, Endometrial and Ovarian cancers for Type B BG (P < 0.05).